2016
DOI: 10.1364/oe.24.025964
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz parametric generation and amplification from potassium titanyl phosphate in comparison with lithium niobate and lithium tantalate

Abstract: We report superior terahertz parametric generation from potassium titanyl phosphate (KTP) over congruent-grown lithium niobate (CLN) and lithium tantalate (CLT) in terms of parametric gain and laser damage resistance. Under the same pump and crystal configurations, the signal emerged first from KTP, 5% Mg-doped CLN, CLN, and then finally from CLT. The signal growth rate in KTP was comparable to that in 5%-Mg-doped CLN, but the signal power from KTP reached a much higher value after all the other crystals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…In recent years, researchers found that the KTP crystal could also be used to obtain THz radiation through the stimulated polariton scattering (SPS) effect [11][12][13][14]. SPS is a special frequency down-converting process which includes both second-order and third-order nonlinear effects [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, researchers found that the KTP crystal could also be used to obtain THz radiation through the stimulated polariton scattering (SPS) effect [11][12][13][14]. SPS is a special frequency down-converting process which includes both second-order and third-order nonlinear effects [15].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained THz pulse energy was 336 nJ at 5.72 THz when the pulse repetition frequency (PRF) was 10 Hz and the pump pulse energy was 80 mJ [11]. In the following years, there were some reports of enhancing the performance of the external cavity-pumped SPS laser using a KTP crystal [12][13][14]. The external cavity-pumped SPS sources are mainly used to generate terahertz pulses with relatively high pulse energy and low pulse repetition rate.Compared with the external cavity-pumped system which requires a high-pulse-energy pumping laser, an intracavity-pumped system, in which the nonlinear crystal is inserted in the fundamental cavity, can take advantage of the high intracavity fundamental power density to enhance nonlinear conversion.…”
mentioning
confidence: 99%
“…using it's quasi-phase matching properties in optical parametric amplifiers [16,17], or as envisaged in [18], pumped with a dual wavelength fiber laser for direct THz conversion through the beat frequency [19]. Recently, THz generation using parametric amplification in KTP was observed [20], and very recently Wu et al demonstrated generation of >100 kW peak power from a KTP THz parametric oscillator [21].…”
Section: Introductionmentioning
confidence: 99%
“…Stimulated polariton scattering (SPS) has proven to be an efficient scheme to generate terahertz (THz) waves [1][2][3][4][5][6][7][8]. A polariton is a coupled quantum between the pump laser and the infrared-and Raman-active transverse optical (TO) modes in a crystal, and it behaves like phonons near the resonant frequency associated with the TO mode and exhibits photon-like behavior for lower non-resonant frequencies [1].…”
Section: Introductionmentioning
confidence: 99%